Contribution of the seagrass Syringodium isoetifolium to the metabolic functioning of a tropical reef lagoon - Olivé, Irene; García-Robledo, Emilio; Silva, João; Pintado-Herrera, Marina G.; Santos, Rui; Kamenos, Nicholas A.; Cuet, Pascale; Frouin, Patrick (Frontiers in Marine Science, 2022)
Seagrasses are gaining attention thanks to their metabolism and potential major role as carbon sinks, with further implications as nature-based solutions against climate change. Despite their recognized importance and the growing number of studies published, there is still a striking paucity of information on seagrass metabolism and contribution to biogeochemical cycles for some seagrass species and ocean areas. In this study we assessed the metabolic balance and nutrient cycling contribution of seagrasses to the benthic compartment of a tropical reef lagoon in Reunion Island, providing original information on a barely studied seagrass species (Syringodium isoetifolium) and a poorly studied ocean region (West Indian Ocean). We measured the net productivity, respiration and the metabolic balance in different components of the lagoon benthic compartment (i.e. seagrass, sediment, and benthic community) and the water-sediment nutrient benthic fluxes at differently impacted sites within the lagoon. The biogeochemical environmental variability, including inorganic and organic indicators of anthropogenic contamination, was also assessed at each site. Large spatial variability was detected in the metabolic balance of each benthic component assessed, also associated with the natural and/or anthropic-driven environmental variability found in the lagoon. The seagrass S. isoetifolium was net autotrophic across the lagoon and contributed to the lagoon benthic metabolism with net plant productivity exceeding by one order of magnitude the plant respiration. The lowest seagrass metabolism was detected at the impacted site. The metabolic balance of the sediment was heterotrophic but the high productivity of S. isoetifolium contributed to reducing the heterotrophy of the whole benthic community. The lagoon-wide benthic metabolic balance was slightly heterotrophic, but the associated uncertainty ranged from autotrophy to heterotrophy. Nutrient concentrations in the lagoon were low and the benthic community capacity for nutrient retention (uptake) and removal (denitrification and anammox) indicated potential for buffering moderate nutrient inputs into the lagoon. Organic contaminants of emerging concern (CECs) were low but detectable in the lagoon, especially in highly frequented beach areas, arising as an environmental quality indicator of interest.